(untitled) (Kinesiology, 2020)
Cognition is a major subject to be addressed nowadays due to the increasing number of cognitively affected people in most societies. Because of a lack of pharmaceutical therapies treating cognitive decline, its indicators should be diagnosed before it becomes prevalent. Scientific evidence indicates a relationship between cognition and the nervous system, especially its autonomic part. Heart rate variability (HRV) as an indicator of the autonomic nervous system functioning has been studied as a biological marker for the evaluation of cognitive performance. Therefore, HRV is a possible indicator of cognitive impairment. The aim was to provide a systematic literature review about the association between resting HRV and the cognitive performance. Five cognitive functions were analysed separately: executive functions, memory and learning, language abilities, visuospatial functioning, and processing speed. Furthermore, the global cognitive function evaluated with cognitive test batteries was considered too. An electronic database search was conducted with five databases. Three search fields comprised HRV, cognitive performance, and adult subjects. The final dataset consisted of 27 articles. Significant correlations in each cognitive function were found, except for processing speed, suggesting a positive association between resting HRV and cognitive performance. Mechanisms underlying this association between cardiovascular health and cognition are discussed. For the future, HRV could be used in diagnostics as an indicator of cognitive impairment before symptoms of dementia get apparent. With a timely diagnosis, preventative tools could be initiated at an early stage of dementia.